Lithium-sodium composite diphosphate positive electrode material, preparation method thereof and positive plate

By using lithium-sodium composite bisphosphate positive electrode material, the matrix unit and carbon cladding layer composed of PO4 tetrahedron, FeO6 octahedron and P2O7 groups, the preparation risks, low-temperature performance and consistency of existing lithium iron phosphate battery positive electrode materials are solved, and efficient lithium-sodium ion transmission and material cost reduction are achieved.

CN119542388APending Publication Date: 2025-02-28ANHUI LEVINENG POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702891.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery positive electrode materials have problems such as high risk in the material preparation process, poor low temperature performance, and poor product consistency. At the same time, the development of lithium resources is difficult to meet the demand, resulting in an increase in battery costs.

Method used

The lithium-sodium composite bisphosphate positive electrode material is used, and its structure is composed of a matrix unit, an electronic conductive layer and an elastomer layer. The matrix unit is composed of PO4 tetrahedron, FeO6 octahedron and P2O7 groups to form an ionic high-speed conductive network with all connections and improves the electronic conductivity and mechanical strength through the carbon cladding layer.

Benefits of technology

It achieves high conductivity, high compaction density, excellent electrochemical performance of the material, and can deintercalate lithium ions and sodium ions at the same time, reducing material costs and improving battery safety and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542388A_ABST
    Figure CN119542388A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion and lithium ion batteries, and discloses a lithium-sodium composite diphosphate positive electrode material, a preparation method thereof and a positive plate, and the structure of the composite material sequentially comprises a matrix unit, an electronic conducting layer and an elastomer layer from inside to outside. The matrix unit is composed of a PO4 tetrahedron, a FeO6 octahedron and a P2O7 group, and the chemical general formula of the material is Li < 3y-2x > Na < 4 > Fe < x > (PO4) < y > (P2O7), 2lt, x is less than or equal to 6, 2lt; y < = 6, 3y-2xgt; 0; the preparation method comprises the following steps: pre-reacting phosphate with ferric salt; preparing a precursor by a coprecipitation method; doping lithium ions and sodium ions, carrying out solid-phase high-temperature reaction, and crushing; the material prepared by the method has the functions of simultaneously deintercalating and intercalating lithium ions and sodium ions, is suitable for large-scale production, is controllable in ion doping amount and thickness and uniformity of an electron conducting layer and an elastomer layer, is good in material consistency, high in compaction density, high in conductivity and excellent in electrochemical performance, and can be applied to the field of electrochemical devices. The method has high popularization and application values in the technical field of lithium-sodium composite batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion and lithium ion batteries, and in particular to a lithium sodium composite biphosphate positive electrode material and a preparation method and a positive electrode sheet thereof. Background Art

[0002] Lithium iron phosphate (LFP) batteries have excellent characteristics such as high safety, long cycle life, high voltage platform, and low self-discharge. They are widely used in various electronic products, automotive power batteries, and energy storage power stations.

[0003] However, the LFP positive electrode material for lithium iron phosphate batteries has the following problems: (1) During the material preparation process, iron oxide is easily reduced to elemental iron in a high-temperature reducing atmosphere, resulting in a high risk of micro-short circuits in the battery; (2) The electronic conductivity of the material is low, resulting in poor low-temperature performance of the battery; (3) Material synthesis is a complex multiphase reaction, resulting in poor product consistency. As the global lithium-ion battery market continues to expand, the development speed of lithium resources has been difficult to meet the growing demand, resulting in rising battery costs. Sodium-ion batteries have attracted widespread attention due to their high resource abundance, low cost, and excellent low-temperature performance. From the perspective of technical routes, the positive electrodes of sodium-ion batteries mainly include layered oxides, polyanions, and Prussian blue / white compounds, each of which has its own advantages and disadvantages in performance. Prussian blue / white materials contain crystal water that is difficult to remove, resulting in a low battery cycle life; layered oxides are easy to absorb water, the battery process technology requirements are strict, and the high-temperature cycle is poor. In addition, the material usually contains copper or nickel, and the primary cost is relatively high; polyanion materials have problems such as poor conductivity and low compaction density. According to market demand, there is an urgent need to develop new positive electrode materials to further improve the electrochemical performance of batteries, reduce costs, and improve the safety of materials during use, so as to meet the needs of the new energy field for secondary battery materials. Summary of the invention

[0004] The object of the present invention is to provide a lithium sodium composite diphosphate positive electrode material and a preparation method and a positive electrode sheet thereof, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: a lithium sodium composite biphosphate positive electrode material, whose structure from inside to outside is: a matrix unit, an electronic conductive layer and an elastic layer, the matrix unit is composed of PO4 tetrahedron, FeO6 octahedron and P2O7 group; two coating layers outside the matrix, the coating layers are electronic conductive layer and elastic layer from inside to outside;

[0006] PO4 tetrahedron, FeO6 octahedron and P2O7 group form a high-speed ion conductive network extending in all directions, ensuring the ion transmission path, which is beneficial to Na + / Li +The embedding and extraction of ions; the conductive layer coated on the second outer layer has a directional continuous pore structure, forming a fast electronic conductive network; the elastomer layer coated on the outermost layer is stacked with a weaker van der Waals force, which increases the overall mechanical strength and compressive strength of the material, improves the compaction density of the material, and avoids direct contact between the composite material and the electrolyte, inhibiting interface side reactions and metal ion dissolution;

[0007] The general chemical formula of the positive electrode material is Li 3y-2x Na4Fe x (PO4) y (P2O7), 2 <x≤6,2<y≤6,3y-2x> 0.

[0008] Preferably, the particle size of the positive electrode material is 0.1 to 1 μm, the average particle size is concentrated in the range of 100 to 500 nm, and the specific surface area of ​​the positive electrode material is 1 to 50 m 2 / g; the powder compaction density of the positive electrode material is 2.0~2.7g / cm 3 .

[0009] Preferably, the main component of the conductive layer is one or a mixture of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.

[0010] Preferably, the main component of the elastomer layer is one or a mixture of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), fluorine-containing polymer system polyvinylidene fluoride (PVDF) and vinylidene fluoride-hexafluoropropylene (HFP).

[0011] Preferably, the mass ratio of the elastomer layer, the conductive layer and the substrate is (0.01-0.1):(0.01-0.1):1.

[0012] Preferably, the thickness of the conductive layer is 1 to 15 nm, and the thickness of the elastomer layer is 0.1 to 2 nm.

[0013] According to the experimental results of the present invention, too little coating will not significantly improve the electrochemical performance, while too much coating will destroy the spatial structure of the raw material itself, causing the material structure to be unstable. By controlling the doping amount and thickness of the elastomer layer and the conductive layer, it is possible to effectively ensure that the specific surface area of ​​the composite electrode material is moderate and the uniformity of the composite electrode material particles is ensured, thereby effectively ensuring the electrochemical performance of the target product.

[0014] The method for preparing a lithium sodium composite biphosphate positive electrode material comprises the following steps:

[0015] S1: stirring a certain amount of phosphate and iron salt in a solvent for pre-reaction;

[0016] S2: then add alkali solution under heating conditions to carry out precipitation reaction, and then obtain precursor A through solid-liquid separation, washing and drying;

[0017] S3: After the lithium salt, the sodium salt and the precursor A are uniformly mixed in a certain proportion, a high-temperature solid-phase reaction is carried out under an inert atmosphere, and then the pre-product B is obtained after crushing and sieving;

[0018] S4: B is filled into a fluidized bed reactor with an inner diameter of 100 mm, and after heating to a certain temperature at a specific heating rate, a carbon source is introduced and reacted for a period of time, and the product is collected after naturally cooling to room temperature to obtain a pre-product C modified with a carbon-coated electronic conductive layer;

[0019] S5: gradually add the polymer powder into the solvent while stirring, completely immerse C in the polymer solution, and then dry and solidify at a certain temperature to obtain the target product.

[0020] Preferably, the phosphate in S1 is selected from one of diammonium phosphate or diammonium pyrophosphate, or a combination of diammonium phosphate and diammonium pyrophosphate; the iron salt in S1 comprises one or more of ferrous nitrate, ferrous chloride, ferrous acetate or ferrous oxalate;

[0021] The pre-reaction temperature in S1 ranges from 25 to 60°C, and the reaction time ranges from 60 to 180 minutes.

[0022] Preferably, the lithium salt in S3 comprises one or more of lithium hydroxide, lithium carbonate, lithium acetate or lithium oxalate; the sodium source is selected from at least one of sodium oxalate, sodium carbonate, sodium hydrogen pyrophosphate and disodium hydrogen phosphate;

[0023] The molar ratio of Li in the lithium source, Na in the sodium source, Fe in the iron source and P in the phosphorus source in S3 and S1 is: Li:Na:Fe:P=(0.5-2.5):(4-4.2):(3.5-5.5):(4.5-6.5);

[0024] The high temperature solid phase reaction in S3 adopts the following heating program: (I) room temperature to 500°C, heating rate 10°C / min; (II) 300 to 800°C, heating rate 5°C / min, heat preservation for 1 to 10 hours; (III) 500 to 1000°C, heating rate 3°C / min, heat preservation for 1 to 10 hours; the sintering treatment atmosphere includes one of helium and argon; the crushing adopts air flow crushing, and the particle size after crushing is 0.1 to 1um;

[0025] In S4, the atmosphere is nitrogen or argon inert atmosphere, the temperature is 800-1000°C, the carbon source is methane or at least one of ethane and acetylene, and the carbon source gas is introduced into the reactor at a volume ratio of 1:1 to 1:4 to the inert gas, the total flux is 500-900h-1, and the system is maintained at this temperature for 60-600min;

[0026] The polymer powder in S5 comprises one or a mixture of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), a fluorine-containing polymer system polyvinylidene fluoride (PVDF) and vinylidene fluoride-hexafluoropropylene (HFP); the solvent comprises one or a mixture of ethanol, n-propanol, isopropanol, acetone, N-methylpyrrolidone, dimethylsulfamide, dimethyl sulfoxide, and xylene;

[0027] In S5, the drying temperature is 25-150°C and the curing time is 10-48h.

[0028] Carbon-coated nanoparticles prepared by chemical vapor deposition have the characteristics of uniform size, and the porous structure can increase the contact area between the active material and the electrolyte, which is conducive to improving the migration rate of electrons and ions. The carbon layer has its unique electronic network structure, which can also achieve rapid migration of electrons, thereby improving the electrochemical performance of the battery. In the present invention, the thickness and continuity of the carbon coating layer are controlled by controlling the process parameters of the carbon coating process, such as: carbon source, heating rate, gas flow rate, coating temperature and time, thereby achieving the purpose of improving the electronic conductivity of the material.

[0029] A positive electrode sheet, comprising: a current collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one surface of the current collector; the positive electrode active layer is obtained by coating a positive electrode active slurry on the current collector, wherein the positive electrode active slurry comprises the lithium sodium composite bisphosphate positive electrode material according to any one of claims 1 to 9;

[0030] The positive electrode active slurry also includes a conductive agent and a binder, and the mass percentages of the positive electrode material, the conductive agent and the binder are (85-95%): (0.5-10%): (0.5-4.5%).

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention discloses a composite positive electrode material capable of simultaneously deintercalating lithium ions and sodium ions, which enriches the types of positive electrode materials for secondary batteries. The material has a novel structure, comprising a matrix unit, an electronic conductive layer and an elastomer layer. The matrix unit is composed of PO4 tetrahedron, FeO6 octahedron and P2O7 group. PO4 tetrahedron, FeO6 octahedron and P2O7 group form an ion high-speed conductive network extending in all directions, ensuring the Na + / Li +Ion transmission path; the electronic conductive layer has a directional continuous pore structure, forming a fast electronic conductive network; the elastomer layer is stacked with a weaker van der Waals force, which increases the overall mechanical strength and compressive resistance of the material, improves the compaction density of the material, and avoids direct contact between the composite material and the electrolyte, inhibiting interfacial side reactions and metal ion dissolution.

[0033] The method of the present invention is not only simple to prepare, has mild process conditions, and is suitable for large-scale production, but also has controllable ion doping amount, coating layer thickness and uniformity, and high product consistency.

[0034] The material prepared by this method has high electrical conductivity and high compaction density, and has promotion and application value in the field of lithium-sodium composite battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the lithium-sodium composite positive electrode material provided in Example 1 of the present invention;

[0036] Figure 2 HRTEM image of the lithium-sodium composite positive electrode material provided in Example 1 of the present invention;

[0037] Figure 3 XRD diagram of the lithium-sodium composite positive electrode material provided in Example 1-2 of the present invention;

[0038] Figure 4 A charge and discharge curve diagram of a lithium-sodium composite positive electrode material provided in Example 2 of the present invention;

[0039] Figure 5 A charge and discharge curve diagram of the lithium-sodium composite positive electrode material provided in Examples 1-3 of the present invention;

[0040] Figure 6 The charge and discharge curve of the positive electrode material for the hard carbon negative electrode 3Ah soft pack obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0042] Example 1

[0043] (1) Dissolve 0.4 mol of diammonium dihydrogen phosphate, 0.1 mol of diammonium hydrogen pyrophosphate and 0.5 mol of ferrous chloride in 200 ml of deionized water and pre-react at 50° C. with stirring for 90 min.

[0044] (2) At room temperature, ammonia water is added dropwise to the above solution, and the pH is adjusted to 10 to perform a precipitation reaction, followed by solid-liquid separation, washing, and drying to obtain precursor A.

[0045] (3) Then, 0.11 mol of lithium carbonate and 0.2 mol of sodium carbonate were dry-mixed with the precursor, and the reaction was carried out in an argon atmosphere using the following programmed temperature increase reaction: (I) room temperature to 500°C, a heating rate of 10°C / min; (II) the temperature was continued to be increased to 800°C, a heating rate of 5°C / min, and the temperature was kept for 5 hours; (III) the temperature was continued to be increased to 1000°C, a heating rate of 3°C / min, and the temperature was kept for 3 hours; the pre-product B was obtained by air flow crushing with an average particle size of 0.3 to 0.5 um after screening.

[0046] (4) The above substrate was filled into a fluidized bed reactor with an inner diameter of 100 mm, and methane carbon source gas and inert gas were introduced into the reactor at a volume ratio of 1:1. The total flux was 900 h -1 When the temperature is raised to 900°C at a heating rate of 10°C / min, the reaction is kept at this temperature for 480 minutes, and then the pre-product C containing the conductive layer modification is obtained after cooling to room temperature.

[0047] (5) PVDF powder was gradually added into xylene while stirring. The pre-product C was completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product.

[0048] The positive electrode material prepared in this example was ground evenly with the conductive agent SuperP and the binder PVDF according to a mass ratio of 95:3:2, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated 10um aluminum foil, dried in a blast drying oven at 80°C for 12h, and then dried in a vacuum drying oven at 120°C for 12h. Then, a slicing machine was used to cut the positive electrode sheets into 14mm round pieces.

[0049] Example 2

[0050] (1) Dissolve 0.5 mol of diammonium dihydrogen phosphate, 0.2 mol of diammonium hydrogen pyrophosphate and 0.6 mol of ferrous chloride in 200 ml of deionized water and pre-react at 50° C. with stirring for 90 min.

[0051] (2) At room temperature, ammonia water is added dropwise to the above solution, and the pH is adjusted to 10 to perform a precipitation reaction, followed by solid-liquid separation, washing, and drying to obtain precursor A.

[0052] (3) Then, 0.51 mol of lithium carbonate and 0.4 mol of sodium carbonate were dry-mixed with the precursor, and the reaction was carried out in an argon atmosphere using the following programmed temperature increase reaction: (I) room temperature to 500°C, a heating rate of 10°C / min; (II) the temperature was continued to be increased to 800°C, a heating rate of 5°C / min, and the temperature was kept for 5 hours; (III) the temperature was continued to be increased to 1000°C, a heating rate of 3°C / min, and the temperature was kept for 3 hours; the pre-product B was obtained by air flow crushing with an average particle size of 0.3 to 0.5 um after screening.

[0053] (4) The above substrate was filled into a fluidized bed reactor with an inner diameter of 100 mm, and methane carbon source gas and inert gas were introduced into the reactor at a volume ratio of 1:1. The total flux was 900 h -1 When the temperature is raised to 900°C at a heating rate of 10°C / min, the reaction is kept at this temperature for 480 minutes, and then the pre-product C containing the conductive layer modification is obtained after cooling to room temperature.

[0054] (5) PVDF powder was gradually added into xylene while stirring. The pre-product C was completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product.

[0055] The positive electrode material prepared in this example was ground evenly with the conductive agent SuperP and the binder PVDF according to a mass ratio of 95:3:2, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated 10um aluminum foil, dried in a blast drying oven at 80°C for 12h, and then dried in a vacuum drying oven at 120°C for 12h. Then, a slicing machine was used to cut the positive electrode sheets into 14mm round pieces.

[0056] Example 3

[0057] (1) Dissolve 0.3 mol of diammonium dihydrogen phosphate, 0.1 mol of diammonium hydrogen pyrophosphate and 0.4 mol of ferrous chloride in 200 ml of deionized water and pre-react at 50° C. with stirring for 90 min.

[0058] (2) At room temperature, ammonia water is added dropwise to the above solution, and the pH is adjusted to 10 to perform a precipitation reaction, followed by solid-liquid separation, washing, and drying to obtain precursor A.

[0059] (3) Then, 0.51 mol of lithium carbonate and 0.2 mol of sodium carbonate were dry-mixed with the precursor, and the temperature was increased in an argon atmosphere using the following program: (I) room temperature to 500°C, a heating rate of 10°C / min; (II) the temperature was continued to be increased to 800°C, a heating rate of 5°C / min, and the temperature was kept for 5 hours; (III) the temperature was continued to be increased to 1000°C, a heating rate of 3°C / min, and the temperature was kept for 3 hours; the pre-product B was obtained by air flow crushing with an average particle size of 0.3 to 0.5 um after screening.

[0060] (4) The above substrate was filled into a fluidized bed reactor with an inner diameter of 100 mm, and methane carbon source gas and inert gas were introduced into the reactor at a volume ratio of 1:1. The total flux was 900 h -1 When the temperature is raised to 900°C at a heating rate of 10°C / min, the reaction is kept at this temperature for 480 minutes, and then the pre-product C containing the conductive layer modification is obtained after cooling to room temperature.

[0061] (5) PVDF powder was gradually added into xylene while stirring. The pre-product C was completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product.

[0062] The positive electrode material prepared in this example was ground evenly with the conductive agent SuperP and the binder PVDF according to a mass ratio of 95:3:2, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated 10um aluminum foil, dried in a blast drying oven at 80°C for 12h, and then dried in a vacuum drying oven at 120°C for 12h. Then, a slicing machine was used to cut the positive electrode sheets into 14mm round pieces.

[0063] Example 4

[0064] Example 4 provides a positive electrode material. The preparation method is different from that of Example 1 in that: in step (1), the phosphate is selected from 0.5 mol of diammonium dihydrogen phosphate, replacing "0.4 mol of diammonium dihydrogen phosphate and 0.1 mol of diammonium hydrogen pyrophosphate" in step (1) of Example 1.

[0065] Example 5

[0066] Example 5 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: the iron salt in step (1) is selected from 0.5 mol ferrous nitrate, replacing the "0.5 mol ferrous chloride" in step (1) of Example 1.

[0067] Example 6

[0068] Example 6 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: the "preliminary reaction under stirring at 25°C for 60 minutes" in step (1) replaces the "preliminary reaction under stirring at 50°C for 90 minutes" in step (1) of Example 1.

[0069] Example 7

[0070] Example 7 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (2), "at 60°C, dripping ammonia water into the above solution, adjusting the pH to 7 for precipitation reaction" replaces the step (2) of Example 1, "at room temperature, dripping ammonia water into the above solution, adjusting the pH to 10 for precipitation reaction".

[0071] Example 8

[0072] Example 8 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (3), "0.11 mol of lithium hydroxide and 0.2 mol of sodium hydrogen pyrophosphate are dry mixed with the precursor" replaces "0.11 mol of lithium carbonate and 0.2 mol of sodium carbonate are dry mixed with the precursor" in step (3) of Example 1.

[0073] Example 9

[0074] Example 9 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (3), "room temperature ~ 1000°C, heating rate 10°C / min, and heat preservation for 8 hours" is replaced by "(I) room temperature ~ 500°C, heating rate 10°C / min; (II) continue to heat to 800°C, heating rate 5°C / min, and heat preservation for 5 hours; (III) continue to heat to 1000°C, heating rate 3°C / min, and heat preservation for 3 hours" in step (3) of Example 1.

[0075] Example 10

[0076] Example 10 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (4), "a methane carbon source gas and an inert gas in a volume ratio of 1:1 are introduced into the reactor, and the total flux is 900h -1 , when the temperature is raised to 1000°C at a rate of 10°C / min, the reaction is kept warm for 600min", replacing the step (4) of Example 1 in which "methane carbon source gas and inert gas are introduced into the reactor in a volume ratio of 1:1, with a total flux of 900h -1 , when the temperature is raised to 900℃ at a rate of 10℃ / min, the reaction is kept at this temperature for 480min.

[0077] Embodiment 11

[0078] Example 11 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (5), "PMMA powder is gradually added to ethanol while stirring. The pre-product C is completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product" is replaced by "PVDF powder is gradually added to xylene while stirring. The pre-product C is completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product" in step (5) of Example 1.

[0079] Example 12

[0080] Example 12 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in step (5), "PMMA powder is gradually added to ethanol while stirring. The pre-product C is completely immersed in the polymer solution, and then dried and cured at 150°C for 48 hours to obtain the target product" is replaced by "PVDF powder is gradually added to xylene while stirring. The pre-product C is completely immersed in the polymer solution, and then dried and cured at 80°C for 24 hours to obtain the target product" in step (5) of Example 1.

[0081] Example 13

[0082] Example 13 provides a positive electrode material, and the preparation method is different from that of Example 1 in that: in the preparation of the positive electrode sheet, "the positive electrode material and the conductive agent Super P, and the binder PVDF are in a mass ratio of 90:7:3", which replaces the "positive electrode material and the conductive agent Super P, and the binder PVDF are in a mass ratio of 95:3:2" in the electrode sheet composition of Example 1.

[0083] Comparative Example 1

[0084] Commercial lithium iron phosphate material is used as a comparison.

[0085] Comparative Example 2

[0086] Commercial sodium ferric pyrophosphate was used as a comparison.

[0087] Performance Testing

[0088] The performance of the positive electrode materials prepared in the above embodiments and comparative examples was tested.

[0089] The specific method of the button battery is as follows: the positive electrode sheet obtained by the present invention is assembled with metal lithium and metal sodium as the negative electrode to obtain a CR2032 button battery. The battery performance test: the discharge cut-off voltage is 2.0V, and the charge cut-off voltage is 4.0V.

[0090] The specific method of the soft pack battery is as follows: the positive electrode sheet obtained by the present invention is assembled with hard carbon as the negative electrode to obtain a 3Ah soft pack battery, and the electrolyte composition is 1 mol NaPF6 + 1 mol LiPF6 / (EC: DEC = 1: 1). Battery performance test: the discharge cut-off voltage is 2.0V, and the charge cut-off voltage is 4.0V.

[0091] Depend on Figure 1 It can be seen that the material prepared by the present invention generally presents two different particle size ranges. The small particle size range is spherical and the particle size is concentrated in 100-300nm, and the large particle size range is agglomerates and the particle size is concentrated in 0.5-1um. This mixing of large and small particles is helpful for improving the compaction density of the material. The average particle size of the material is concentrated in 100-500nm. Figure 2 It can be seen that the material structure is novel, consisting of two coating layers, the second outer layer is a conductive layer with a thickness of ~15nm, the conductive layer is continuous and dense, and the uniformity is controllable. The outermost layer is an elastomer layer with a thickness of 0.5 to 2nm. Figure 3 It can be seen that the lithium sodium composite bisphosphate positive electrode material is obtained by adopting the method of the present invention.

[0092] Depend on Figure 4 It can be seen that the material prepared by the present invention can charge and discharge metal lithium and metal sodium. Both the charge and discharge curves of metal lithium and metal sodium show two platforms, suggesting that the material has at least two redox pairs. The discharge capacity of the metal sodium negative electrode can be as high as 135mAh / g, which is also significantly higher than the currently commercialized sodium iron phosphate pyrophosphate (95-105mAh / g). Figure 5 It can be seen that the material prepared by the present invention can achieve a discharge capacity of up to 140 mAh / g for a metal lithium negative electrode, a first efficiency of 100%, and a platform voltage of up to 3.4 V. Figure 6 From the data of soft-pack full batteries, it can be seen that this positive electrode material presents two discharge platforms at 3.2~3.4V and 2.8~3.15V for the hard carbon negative electrode, corresponding to lithium desorption and sodium desorption respectively, and has the function of simultaneously de-intercalating and de-intercalating lithium ions and sodium ions.

[0093] Table 1 Comparison of electrical properties of materials obtained in Example

[0094]

[0095]

[0096] As can be seen from Table 1, by optimizing the preparation method, a composite positive electrode material with high conductivity, high compaction density and electrochemical performance better than the currently commercialized lithium iron phosphate and sodium iron pyrophosphate can be obtained.

[0097] In summary, the embodiments of the present invention provide a new positive electrode material, a preparation method and a positive electrode sheet. The material prepared by this method has the function of simultaneously extracting and embedding lithium ions and sodium ions, and is a new type of chemical energy storage material. It has a high value of promotion and application in the field of lithium-sodium composite battery technology. The method of the present invention is not only simple to prepare, low in energy consumption, low in cost, and environmentally friendly, suitable for large-scale production, but also the ion doping amount, the thickness and uniformity of the electronic conductive layer and the elastomer layer are controllable. The material prepared by this method has good consistency, high compaction density, high electrical conductivity, and excellent electrochemical performance.

[0098] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium sodium composite bisphosphate positive electrode material, characterized in that: Its structure from inside to outside is: matrix unit, electronic conductive layer and elastic layer. The matrix unit is composed of PO4 tetrahedron, FeO6 octahedron and P2O7 group. The chemical formula of positive electrode material is Li 3y-2x Na4Fe x (PO4) y (P2O7), 2 <x≤6,2<y≤6,3y-2x> 0.

2. The lithium sodium composite bisphosphate positive electrode material according to claim 1, characterized in that: The particle size of the positive electrode material is 0.1-1um, the average particle size is concentrated in 100-500nm, and the specific surface area of ​​the positive electrode material is 1-50m 2 / g; the powder compaction density of the positive electrode material is 2.0~2.7g / cm 3 .

3. The lithium sodium composite bisphosphate positive electrode material according to claim 1, characterized in that: The main component of the conductive layer is one or a mixture of carbon black, conductive graphite, carbon fiber, carbon nanotube, and graphene.

4. The lithium sodium composite bisphosphate positive electrode material according to claim 1, characterized in that: The main component of the elastic layer is one or a mixture of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, fluorine-containing polymer system polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene.

5. The lithium sodium composite bisphosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the elastomer layer, the conductive layer and the substrate is (0.01-0.1):(0.01-0.1):

1.

6. The lithium sodium composite bisphosphate positive electrode material according to claim 1, characterized in that: The thickness of the conductive layer is 1 to 15 nm, and the thickness of the elastic layer is 0.1 to 2 nm.

7. The method for preparing the lithium sodium composite bisphosphate positive electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: stirring a certain amount of phosphate and iron salt in a solvent for pre-reaction; S2: then add alkali solution under heating conditions to carry out precipitation reaction, and then obtain precursor A through solid-liquid separation, washing and drying; S3: After the lithium salt, the sodium salt and the precursor A are uniformly mixed in a certain proportion, a high-temperature solid-phase reaction is carried out under an inert atmosphere, and then the pre-product B is obtained after crushing and sieving; S4: Fill B into a fluidized bed reactor with an inner diameter of 100 mm, heat it to a certain temperature at a specific heating rate, introduce a carbon source and react for a period of time, then naturally cool it to room temperature and collect the product to obtain a pre-product C modified with a carbon-coated electronic conductive layer; S5: gradually add the polymer powder into the solvent while stirring, completely immerse C in the polymer solution, and then dry and solidify at a certain temperature to obtain the target product.

8. The method for preparing the lithium sodium composite bisphosphate positive electrode material according to claim 7, characterized in that: The phosphate in S1 is selected from one of diammonium phosphate or diammonium pyrophosphate, or a combination of diammonium phosphate and diammonium pyrophosphate; the iron salt in S1 comprises one or more of ferrous nitrate, ferrous chloride, ferrous acetate or ferrous oxalate; The pre-reaction temperature in S1 ranges from 25 to 60°C, and the reaction time ranges from 60 to 180 minutes.

9. The method for preparing a lithium sodium composite bisphosphate positive electrode material according to claim 7, characterized in that: The lithium salt in S3 comprises one or more of lithium hydroxide, lithium carbonate, lithium acetate or lithium oxalate; the sodium source is selected from at least one of sodium oxalate, sodium carbonate, sodium hydrogen pyrophosphate and disodium hydrogen phosphate; The molar ratio of Li in the lithium source, Na in the sodium source, Fe in the iron source and P in the phosphorus source in S3 and S1 is: Li:Na:Fe:P=(0.5-2.5):(4-4.2):(3.5-5.5):(4.5-6.5); The high temperature solid phase reaction in S3 adopts the following heating program: (I) room temperature to 500°C, heating rate 10°C / min; (II) 300 to 800°C, heating rate 5°C / min, heat preservation for 1 to 10 hours; (III) 500 to 1000°C, heating rate 3°C / min, heat preservation for 1 to 10 hours; the sintering treatment atmosphere includes one of helium and argon; the crushing adopts air flow crushing, and the particle size after crushing is 0.1 to 1um; The atmosphere in S4 is nitrogen or argon inert atmosphere, the temperature is 800-1000°C, the carbon source is methane or at least one of ethane and acetylene, and the carbon source gas is introduced into the reactor at a volume ratio of 1:1-1:4 to the inert gas, and the total flux is 500-900h -1 , the system is kept at this temperature for 60 to 600 minutes; The polymer powder in S5 comprises one or a mixture of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, a fluorine-containing polymer system polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene; the solvent comprises one or a mixture of ethanol, acetone, N-methylpyrrolidone, dimethylsulfamide, dimethyl sulfoxide, and xylene; In S5, the drying temperature is 25-150°C and the curing time is 10-48h.

10. A positive electrode plate, characterized in that: include: A current collector and a positive electrode active layer, wherein the positive electrode active layer is disposed on at least one surface of the current collector; the positive electrode active layer is obtained by coating a positive electrode active slurry on the current collector, wherein the positive electrode active slurry comprises the lithium sodium composite bisphosphate positive electrode material according to any one of claims 1 to 9; The positive electrode active slurry also includes a conductive agent and a binder, and the mass percentages of the positive electrode material, the conductive agent and the binder are (85-95%): (0.5-10%): (0.5-4.5%).